2012
DOI: 10.1210/jc.2011-1818
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity to Angiotensin II and Norepinephrine in Human Uterine Arteries

Abstract: Sensitivity to α-stimulation exceeds ANG II in NP and P UA, explaining the differential uteroplacental sensitivity in pregnancy. Because AT(2)R predominate in UA VSM throughout reproduction, this contributes to the inherent refractoriness to ANG II in the uterine vasculature. The increase in UA contractile proteins at term P suggests remodeling, explaining the enhanced contractility seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…If ATR expression by immunoblots reflects binding density, we provide further evidence that ATR expression is unchanged not only in third generation UVSM, but also precaruncular/placental VSM during ovine pregnancy. Similar findings have been observed in human UVSM (42).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…If ATR expression by immunoblots reflects binding density, we provide further evidence that ATR expression is unchanged not only in third generation UVSM, but also precaruncular/placental VSM during ovine pregnancy. Similar findings have been observed in human UVSM (42).…”
Section: Discussionsupporting
confidence: 91%
“…The differences with small mammals may reflect species specificity (37). Importantly, similar findings occur in human UVSM (42).…”
Section: R65supporting
confidence: 53%
See 1 more Smart Citation
“…In contrast, recent studies in isolated umbilical arteries removed from pregnant and non-pregnant women showed that ANG II induced vascular contractions were not altered in the presence of AT2R inhibition. 47 This may implicate species differences in the role of AT2Rs in modulating haemodynamic effects of AT1Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests broad similarities in vascular function in pregnant women and sheep (6,14,36,37,42). Moreover, vasoactive agonists or antagonists can be infused intra-arterially into one uterine horn of pregnant ewes, limiting systemic effects and allowing the contralateral uterine horn to serve as a control (27,35,40).…”
mentioning
confidence: 99%